Stalactitic rhodochrosite from the 25 de Mayo and Nueve veins, Capillitas, Catamarca, Argentina: Physical and chemical variations - Marquez Zavalia, Maria Florencia (2022)
Capillitas is an epithermal vein-type deposit in Argentina known for its mineralogical diversity, with more than one hundred and twenty described minerals, including five new species, and for the presence of banded and stalactitic rhodochrosite. Stalactites occur as single or combined cylinders of different sizes, from a few cm to 1.36 m in length and diameters up to 8 cm. Their cross-sections may show diverse aspects: from simple concentric banding to more intricate textures, whereas their external surface can be smooth, with undulations or with a poker-chip-like texture. The color of the stalactites varies from white to raspberry pink, with occasional brown bands toward the edges corresponding to a variety of rhodochrosite called “capillitite”. The contents of MnO range from 27.50 to 61.71 wt. % as it may be significantly replaced by CaO, FeO, ZnO and MgO. Replacements are reflected in the various shades of pink and brown displayed by this mineral. The different substitutions in the pink specimens exert only a minor influence on the unit cell parameters, whereas, in the brown variety, their size is significantly smaller with average values for pink rhodochrosite (n = 24): a 4.776 Å, c 15.690 Å and a cell volume of 310.3 Å3, whereas, “capillitite” unit-cell parameters (n = 7) are: a = 4.739, c = 15.558 with a unit-cell volume of 302.6 Å3. Conditions of formation of the banded rhodochrosite of the 25 de Mayo vein, obtained from fluid inclusions data, indicate temperatures of 145 ° to 150 °C and salinities of up to 4 wt. % NaCl(eq). The formation of the stalactites is explained by the infiltration of epithermal aqueous liquid, oversa-turated with Mn and bicarbonate, into a transiently vapor-filled, isolated cavity.